Lead paste formula for improving utilization rate of active substances of lead-acid storage battery and preparation method

By adopting new lead paste formula and preparation process in lead-acid batteries, the problems of low utilization rate of negative electrode active substances and degradation of low temperature performance are solved, and efficient electrochemical performance and starting capability are achieved.

CN119560556AActive Publication Date: 2025-03-04HUBEI HONGBEN ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411736648.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

While the existing lead-acid batteries improve the utilization rate of negative electrode active substances, their low-temperature performance and discharge performance are degraded, making it difficult to meet the demand for starter lead-acid batteries.

Method used

A new lead paste formula is adopted, including lead powder, dilute sulfuric acid solution, short fiber, lignin, carbon black, carbon nanotubes and barium sulfate. By adjusting the formula ratio and preparation process, the conductive properties and pore structure of the negative lead paste are improved.

Benefits of technology

While improving the utilization rate of negative active substances of lead-acid battery, it maintains good low-temperature performance and discharge performance, and enhances the starting capability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a lead paste formula for improving the utilization rate of active substances of a lead-acid storage battery and a preparation method. Belongs to the technical field of lead-acid storage batteries. The invention mainly solves the problem that the low-temperature discharge performance of the battery can be reduced when the utilization rate of the negative electrode active material is improved at present. The battery is mainly characterized in that the formula of the negative lead paste comprises the following components in parts by weight: 100 parts of lead powder, 45-60 parts of 1.15 g / ml-1. 20 g / ml dilute sulphuric acid solution, 0.12-0.2 part of short fiber, 0.5-0.8 part of lignin, 0.3-0.5 part of carbon black, 0.3-0.5 part of carbon nano tube and 0.8-1 part of barium sulfate. The negative electrode lead paste has the characteristics of high water content, high porosity, improvement of a conductive network of the negative electrode lead paste, improvement of the utilization rate of a negative electrode active substance and guarantee of good low-temperature performance of the starting lead-acid storage battery, and is mainly used for improving the utilization rate of the negative electrode active substance of the starting lead-acid storage battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a lead paste formula and a preparation method for improving the utilization rate of active substances in lead-acid batteries. Background Art

[0002] Chinese patent CN 117855406 A discloses a conductive polymer / acetylene black composite material for lead-acid battery negative electrode, lead-acid battery negative electrode, lead-acid battery and related preparation methods: the conductive polymer is grown on the surface of acetylene black by in-situ polymerization, the conductive polymer / acetylene black composite material presents the form of conductive polymer coated acetylene black particles, the acetylene black particles are spherical structures, and the conductive polymer fibers can be clearly observed in the SEM image. The conductive polymer is polyaniline and / or polypyrrole. Modifying acetylene black with conductive polymer materials such as polyaniline can effectively increase the hydrogen evolution overpotential of acetylene black, thereby improving the electrochemical performance of lead-acid batteries. When used as a negative electrode additive for lead-acid batteries, it can effectively increase the discharge specific capacity and cycle life of lead-acid batteries.

[0003] Chinese patent CN 114335537 B discloses a polypyrrole-coated conductive carbon black / indium oxide composite material and its preparation method and application: the composite material has a core-shell structure, the shell material is polypyrrole; the core material is conductive carbon black and indium oxide; the chemical formula of the composite material is [PPy@(C / In2O3)]; the mass ratio of conductive carbon black, polypyrrole and indium oxide is (5-40):(2-8):1. The polypyrrole-coated conductive carbon black / indium oxide composite material, as a negative electrode additive for lead-acid batteries, constructs a hydrophilic three-dimensional ion transport network structure at the negative electrode, effectively improves the "sulfation" phenomenon of the negative electrode of the lead-acid battery, and improves the cycle life of the lead-acid battery at a high rate partial charge state.

[0004] Chinese patent CN 115911379 A discloses a graphene battery negative electrode material and a preparation method thereof: comprising the following steps: adding an auxiliary agent and an alkylsiloxane to a polytetrafluoroethylene emulsion, stirring to obtain a binder; adding three-dimensional graphene, barium sulfate, an organic additive and lead powder to an ethanol aqueous solution, stirring, adding a binder, continuing to stir, obtaining a slurry, spray drying, and obtaining a powder; dispersing fibers in deionized water to obtain a dispersion, adding the dispersion and the above-mentioned powder to a paste machine, stirring, adding a 45-51wt% sulfuric acid solution, and continuing to stir to obtain a lead paste; coating the above-mentioned lead paste on a lead-acid battery grid, drying, and obtaining a graphene battery negative electrode material; selecting three-dimensional graphene as a conductive agent, combined with a homemade binder, achieving close combination and uniform distribution of active substances and carbon powder, and giving the negative electrode material excellent mechanical properties and electrochemical properties.

[0005] The role of polyaniline, polypyrrole, polytetrafluoroethylene, etc. in the above patents is to use these substances to form a framework of highly conductive carbon materials to form a chain-like conductive network. However, the conductivity of polyaniline, polypyrrole, polytetrafluoroethylene, etc. themselves is far lower than that of carbon materials, which greatly reduces the improvement effect.

[0006] When the negative electrode active material (or the amount of negative electrode paste) in the battery is limited, if the utilization rate of the negative electrode active material is to be increased (the amount of negative electrode paste is reduced), the low temperature performance and discharge performance of the battery will decrease. Summary of the invention

[0007] The purpose of the present invention is to provide a negative electrode lead paste and a preparation method thereof, which can improve the utilization rate of negative electrode active materials and ensure good low temperature performance of starting lead-acid batteries in view of the above-mentioned shortcomings.

[0008] The technical solution of the lead paste formula of the present invention is: a lead paste formula for improving the utilization rate of active materials in lead-acid batteries, which is used to improve the utilization rate of negative electrode active materials in starting lead-acid batteries, and is characterized in that the formula of the negative electrode lead paste is as follows by weight: 100 parts of lead powder, 45-60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12-0.2 parts of short fibers, 0.5-0.8 parts of lignin, 0.3-0.5 parts of carbon black, 0.3-0.5 parts of carbon nanotubes, and 0.8-1 parts of barium sulfate.

[0009] The lead powder described in the technical solution of the lead paste formula of the present invention is lead powder with an oxidation degree of 75%.

[0010] The formula of the negative electrode lead paste in the technical solution of the lead paste formula of the present invention is as follows by weight: 100 parts of lead powder, 50-60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.16-0.2 parts of short fibers, 0.5-0.6 parts of lignin, 0.3-0.4 parts of carbon black, 0.3-0.4 parts of carbon nanotubes, and 0.9-1 parts of barium sulfate.

[0011] The formula of the negative electrode lead paste in the technical solution of the lead paste formula of the present invention is as follows by weight: 100 parts of lead powder, 60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.2 parts of short fibers, 0.5 parts of lignin, 0.3 parts of carbon black, 0.3 parts of carbon nanotubes, and 1 part of barium sulfate.

[0012] The formula of the negative electrode lead paste in the technical solution of the lead paste formula of the present invention is as follows by weight: 100 parts of lead powder, 45-50 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12-0.16 parts of short fibers, 0.6-0.8 parts of lignin, 0.4-0.5 parts of carbon black, 0.4-0.5 parts of carbon nanotubes, and 0.8-0.9 parts of barium sulfate.

[0013] The formula of the negative electrode lead paste in the technical solution of the lead paste formula of the present invention is as follows by weight: 100 parts of lead powder, 45 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12 parts of short fibers, 0.8 parts of lignin, 0.5 parts of carbon black, 0.5 parts of carbon nanotubes, and 0.8 parts of barium sulfate.

[0014] The formula of the negative electrode lead paste in the technical solution of the lead paste formula of the present invention is as follows by weight: 100 parts of lead powder, 52-58 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.17-0.19 parts of short fibers, 0.5-0.6 parts of lignin, 0.3-0.4 parts of carbon black, 0.3-0.4 parts of carbon nanotubes, and 0.9-1 parts of barium sulfate.

[0015] The mass ratio of the 1.15g / ml-1.20g / ml dilute sulfuric acid solution to the lead powder in the technical solution of the lead paste formula of the present invention is 12.5%-13.5%; the apparent density of the negative electrode lead paste and the negative electrode lead paste after the paste is completed is 3.60g / ml-3.80g / ml; the water content of the negative electrode lead paste is 14.5%-17.0%.

[0016] The basic particle size of the carbon black in the technical solution of the lead paste formula of the present invention is between 30nm and 300nm, the OAN oil absorption value is between 80ml / 100g and 120ml / 100g, and the nitrogen adsorption specific surface area is 70m 2 / g-90m 2 / g; the diameter of the carbon nanotube is 20nm-100nm, and the length is 10um-50um.

[0017] The lignin in the technical solution of the lead paste formula of the present invention is a single lignin or multiple lignins; the solubility of at least one lignin in the single lignin or multiple lignins in a 1.29 g / ml dilute sulfuric acid solution at 25°C does not exceed 300 mg / L.

[0018] The technical solution of the preparation method of the present invention is: a lead paste preparation method for improving the utilization rate of active materials in lead-acid batteries, characterized in that the negative electrode paste process is: firstly, short fibers, lignin, carbon black, carbon nanotubes and barium sulfate are put into a paste machine, then about 30% of dilute sulfuric acid is added into the paste machine within 2 minutes, the paste machine starts the stirring function while adding the dilute sulfuric acid, then lead powder is added into the paste machine within 2 minutes, and the stirring is continued, and after the lead powder is added, the remaining about 70% of the 1.15-1.25g / ml dilute sulfuric acid solution is added, and the time of adding the dilute sulfuric acid is controlled to be about 15-20 minutes, and during the second addition of dilute sulfuric acid, the paste machine is turned on to evacuate, and the temperature inside the paste machine is controlled not to exceed 60°C; after the acid addition is completed, the vacuum is stopped, the inside of the paste machine is restored to normal pressure, the lead paste is continued to be stirred for about 3-5 minutes, and the paste is finished.

[0019] Traditional carbon materials have a spherical particle structure. After mixing with paste, they exist in a point-like distribution in the negative electrode lead paste, which is not conducive to forming a coherent conductive network. However, carbon nanotube slurry as a negative electrode additive is conducive to forming a carbon chain structure and enhancing the conductivity between negative electrode materials. At the same time, compared with traditional spherical particle structure carbon materials, the addition of carbon nanotubes has less effect on the increase of hydrogen evolution in the negative electrode lead paste. On the other hand, increasing the amount of lignin added can inhibit hydrogen evolution at the negative electrode while ensuring low-temperature performance.

[0020] In the prior art, the mass ratio of sulfuric acid to lead powder in the lead paste of starter lead-acid batteries is generally within 3.5%-7%, and even the research data in the literature do not exceed 12%. The mass ratio of sulfuric acid to lead powder in the lead paste of the present invention generally reaches 12.5%-13%.

[0021] In the prior art, sulfuric acid added in the lead paste process of starting lead-acid batteries generally has a density of 1.35 g / ml-1.40 g / ml. The present invention uses a dilute sulfuric acid solution with a density of 1.15 g / ml-1.20 g / ml.

[0022] In the prior art, the preparation process of lead paste for starter lead-acid batteries is generally as follows: adding auxiliary materials, adding pure water, adding lead powder, adding dilute sulfuric acid, continuously stirring, and finishing with paste. The preparation process of the lead paste of the present invention is as follows: adding auxiliary materials, adding about 30% of the amount of dilute sulfuric acid, adding lead powder, adding the remaining about 70% of the dilute sulfuric acid, continuously stirring, and finishing with paste.

[0023] The beneficial effects of the present invention are: The present invention significantly increases the amount of sulfuric acid added during the preparation of the negative electrode lead paste, and prepares a negative electrode lead paste with high water content and high porosity; carbon nanotubes are used to improve the conductive network of the negative electrode lead paste, improve the effective connection between the negative electrode active materials, and partially offset the effect of the conductive network deterioration caused by the shrinkage of the negative electrode active materials after the battery is charged. The present invention can improve the utilization rate of the negative electrode active materials while ensuring good low temperature performance of the starting lead-acid battery.

[0024] The invention is mainly used for improving the utilization rate of the negative electrode active material of the starting lead-acid battery. DETAILED DESCRIPTION

[0025] The embodiments of the present invention are described in further detail below.

[0026] The invention discloses a lead paste formula for improving the utilization rate of active materials in a lead-acid battery, which is used for improving the utilization rate of negative active materials in a starting lead-acid battery. The formula of the negative lead paste comprises, by weight: 100 parts of lead powder, 45-60 parts of a 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12-0.2 parts of short fibers, 0.5-0.8 parts of lignin, 0.3-0.5 parts of carbon black, 0.3-0.5 parts of carbon nanotubes and 0.8-1 parts of barium sulfate.

[0027] The optimized formula of negative lead paste is as follows by weight: 100 parts of lead powder, 50-60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.16-0.2 parts of short fibers, 0.5-0.6 parts of lignin, 0.3-0.4 parts of carbon black, 0.3-0.4 parts of carbon nanotubes, and 0.9-1 parts of barium sulfate; or 100 parts of lead powder, 52-58 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.16-0.2 parts of short fibers, 0.5-0.6 parts of lignin, 0.3-0.4 parts of carbon black, 0.3-0.4 parts of carbon nanotubes, and 0.9-1 parts of barium sulfate. .17-0.19 parts, lignin 0.5-0.6 parts, carbon black 0.3-0.4 parts, carbon nanotubes 0.3-0.4 parts, and barium sulfate 0.9-1 parts; or lead powder 100 parts, 1.15g / ml-1.20g / ml dilute sulfuric acid solution 45-50 parts, short fibers 0.12-0.16 parts, lignin 0.6-0.8 parts, carbon black 0.4-0.5 parts, carbon nanotubes 0.4-0.5 parts, and barium sulfate 0.8-0.9 parts.

[0028] Among them, the mass ratio of 1.15g / ml-1.20g / ml dilute sulfuric acid solution to lead powder is 12.5%-13.5%; the apparent density of the negative electrode lead paste and the negative electrode lead paste after the paste is 3.60g / ml-3.80g / ml; the water content of the negative electrode lead paste is 14.5%-17.0%; the basic particle size of carbon black is between 30nm-300nm, the OAN oil absorption value is 80ml / 100g-120ml / 100g, and the nitrogen adsorption specific surface area is 70m 2 / g-90m2 / g; the diameter of the carbon nanotube is 20nm-100nm, and the length is 10um-50um; the lignin is a single lignin or a plurality of lignins; the solubility of at least one lignin in the single lignin or the plurality of lignins in a dilute sulfuric acid solution of 1.29g / ml at 25°C does not exceed 300mg / L.

[0029] The invention discloses a method for preparing a lead paste for improving the utilization rate of the negative electrode active material of a starting lead-acid battery. The negative electrode paste making process comprises the following steps: firstly, short fibers, lignin, carbon black, carbon nanotubes and barium sulfate are put into a paste making machine, then, about 30% of dilute sulfuric acid is added into the paste making machine within 2 minutes, the paste making machine starts a stirring function while adding the dilute sulfuric acid, then, lead powder is added into the paste making machine within 2 minutes, the stirring is continued, after the lead powder is added, the remaining about 70% of a 1.15-1.25 g / ml dilute sulfuric acid solution is added, the adding time of the dilute sulfuric acid is controlled to be about 15-20 minutes, during the second adding of the dilute sulfuric acid, the paste making machine starts vacuuming, and the internal temperature of the paste making machine is controlled not to exceed 60 DEG C; after the acid addition is completed, the vacuuming is stopped, the internal pressure of the paste making machine is restored to normal pressure, the lead paste is continuously stirred for about 3-5 minutes, and the paste making is completed.

[0030] Example 1 Negative electrode lead paste formula materials: 100kg lead powder with an oxidation degree of 75%, 60kg dilute sulfuric acid solution with a density of 1.15g / ml, 0.2kg short fiber, 0.5kg lignin, 0.3kg carbon black, 0.3kg carbon nanotubes, and 1kg barium sulfate.

[0031] Negative lead paste and paste process: first put short fibers, lignin, carbon black, carbon nanotubes and barium sulfate into the paste machine, then add 20kg of dilute sulfuric acid into the paste machine within 2 minutes, and start the stirring function of the paste machine while adding dilute sulfuric acid. Then add 100kg of lead powder into the paste machine within 2 minutes, and continue stirring. After the lead powder is added, start adding the remaining 40kg of 1.15g / ml dilute sulfuric acid solution. The time for adding dilute sulfuric acid is controlled to 20 minutes. During the second addition of dilute sulfuric acid, the paste machine is turned on to evacuate, and the maximum temperature inside the paste machine is 55°C; after the acid is added, stop evacuating, and the internal pressure of the paste machine is restored to normal pressure. Continue stirring the lead paste for 3 minutes, and the paste is finished. The apparent density of the lead paste is measured to be 3.65g / ml, and the moisture content of the lead paste is measured to be 16.8%.

[0032] Example 2 Negative electrode lead paste formula materials: 100kg lead powder with an oxidation degree of 75%, 45kg dilute sulfuric acid solution with a density of 1.20g / ml, 0.12kg short fiber, 0.8kg lignin, 0.5kg carbon black, 0.5kg carbon nanotubes, and 0.8kg barium sulfate.

[0033] Negative lead paste and paste process: first put short fibers, lignin, carbon black, carbon nanotubes and barium sulfate into the paste machine, then add 15kg of dilute sulfuric acid into the paste machine within 2 minutes, and start the stirring function of the paste machine while adding dilute sulfuric acid. Then add 100kg of lead powder into the paste machine within 2 minutes, and continue stirring. After the lead powder is added, start adding the remaining 30kg of 1.20g / ml dilute sulfuric acid solution. The time for adding dilute sulfuric acid is 15 minutes. During the second addition of dilute sulfuric acid, the paste machine is turned on to evacuate, and the maximum temperature inside the paste machine is 60℃; after the acid is added, stop evacuating, and the inside of the paste machine returns to normal pressure. Continue stirring the lead paste for 5 minutes, and the paste is finished. The apparent density of the lead paste is measured to be 3.78g / ml, and the moisture content of the lead paste is measured to be 14.6%.

[0034] Comparative ratio (current) Negative electrode lead paste formula materials: 100kg lead powder with an oxidation degree of 75%, 10kg dilute sulfuric acid solution with a density of 1.38g / ml, 12kg pure water, 0.08kg short fiber, 0.3kg lignin, 0.3kg carbon black, and 0.8kg barium sulfate.

[0035] Negative lead paste and paste process: first put short fiber, lignin, carbon black, and barium sulfate into the paste machine, then add 11kg of pure water into the paste machine within 2 minutes, and start the stirring function of the paste machine while adding pure water. Then add 100kg of lead powder into the paste machine within 2 minutes, and continue stirring. After the lead powder is added, start adding 10kg of 1.38g / ml dilute sulfuric acid solution. The time for adding dilute sulfuric acid is 15 minutes. During the process of adding dilute sulfuric acid, the paste machine starts vacuuming, and the maximum temperature inside the paste machine is 60℃; after the acid is added, stop vacuuming, and the inside of the paste machine returns to normal pressure. Continue stirring the lead paste for 5 minutes, and the paste is finished. The apparent density of the lead paste is measured to be 4.35g / ml, and the moisture content of the lead paste is measured to be 11.8%.

[0036] The mass ratio of sulfuric acid to lead oxide in the negative electrode lead paste formula of Example 1 and Example 2 is about 13%, and the mass ratio of sulfuric acid to lead oxide in the negative electrode lead paste formula of the comparative example is about 5%.

[0037] The negative electrode lead paste prepared in Example 1, Example 2, and the comparative example was coated on the plates at a coating amount of 95 g / piece, and was prepared into a 100Ah SLI battery according to the electrode group structure of 9 positive plates and 8 negative plates using the current conventional positive plates (paste coating amount of 100 g / piece). The C20 capacity and Cre capacity (reserve capacity) of the battery were tested in accordance with "GBT5008.1-2023 Starting lead-acid batteries Part 1 Technical conditions and test methods".

[0038] The capacity test data is shown in the following table: Compared with the comparative example, the C20 capacity and Cre capacity (reserve capacity) of Examples 1 and 2 are both improved, especially the Cre capacity (reserve capacity) is significantly improved. The initial Cre capacity of Example 1 is increased by about 8% compared with the comparative example, and the initial Cre capacity of Example 2 is increased by about 13.6% compared with the comparative example.

[0039] The above embodiments provide a detailed introduction to a lead paste formula and a preparation method thereof for improving the utilization rate of active materials in lead-acid batteries provided by the present invention. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A lead paste formula for improving the utilization rate of active materials in lead-acid batteries, which is used to improve the utilization rate of negative active materials in starting lead-acid batteries, and is characterized by: The formula of the negative electrode lead paste is as follows by weight: 100 parts of lead powder, 45-60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12-0.2 parts of short fibers, 0.5-0.8 parts of lignin, 0.3-0.5 parts of carbon black, 0.3-0.5 parts of carbon nanotubes, and 0.8-1 parts of barium sulfate.

2. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to claim 1 is characterized by: The lead powder has an oxidation degree of 75%.

3. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to claim 1 or 2, characterized in that The formula of the negative electrode lead paste is as follows by weight: 100 parts of lead powder, 50-60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.16-0.2 parts of short fibers, 0.5-0.6 parts of lignin, 0.3-0.4 parts of carbon black, 0.3-0.4 parts of carbon nanotubes, and 0.9-1 parts of barium sulfate.

4. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to claim 3 is characterized in that The formula of the negative electrode lead paste is as follows by weight: 100 parts of lead powder, 60 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.2 parts of short fibers, 0.5 parts of lignin, 0.3 parts of carbon black, 0.3 parts of carbon nanotubes, and 1 part of barium sulfate.

5. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to claim 1 or 2, characterized in that The formula of the negative electrode lead paste is as follows by weight: 100 parts of lead powder, 45-50 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12-0.16 parts of short fibers, 0.6-0.8 parts of lignin, 0.4-0.5 parts of carbon black, 0.4-0.5 parts of carbon nanotubes, and 0.8-0.9 parts of barium sulfate.

6. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to claim 5, characterized in that The formula of the negative electrode lead paste is as follows by weight: 100 parts of lead powder, 45 parts of 1.15g / ml-1.20g / ml dilute sulfuric acid solution, 0.12 parts of short fibers, 0.8 parts of lignin, 0.5 parts of carbon black, 0.5 parts of carbon nanotubes, and 0.8 parts of barium sulfate.

7. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to any one of claims 1-2, 4, and 6, characterized in that: The mass ratio of the 1.15g / ml-1.20g / ml dilute sulfuric acid solution to the lead powder is 12.5%-13.5%; the apparent density of the negative electrode lead paste and the negative electrode lead paste after the paste is completed is 3.60g / ml-3.80g / ml; the water content of the negative electrode lead paste is 14.5%-17.0%.

8. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to any one of claims 1-2, 4, and 6, characterized in that: The basic particle size of the carbon black is between 30nm and 300nm, the OAN oil absorption value is between 80ml / 100g and 120ml / 100g, and the nitrogen adsorption specific surface area is 70m 2 / g-90m 2 / g; the diameter of the carbon nanotube is 20nm-100nm, and the length is 10um-50um.

9. The lead paste formula for improving the utilization rate of active materials in lead-acid batteries according to any one of claims 1-2, 4, and 6, characterized in that: The lignin is a single lignin or a plurality of lignins; the solubility of at least one lignin among the single lignin or the plurality of lignins in a 1.29 g / ml dilute sulfuric acid solution at 25° C. is no more than 300 mg / L.

10. A method for preparing the lead paste for improving the utilization rate of active materials in lead-acid batteries according to any one of claims 1 to 9, characterized in that The negative electrode paste process is as follows: first put short fibers, lignin, carbon black, carbon nanotubes and barium sulfate into the paste machine, then add about 30% of dilute sulfuric acid into the paste machine within 2 minutes, start the stirring function of the paste machine while adding the dilute sulfuric acid, then add lead powder into the paste machine within 2 minutes, continue stirring, and after the lead powder is added, start adding the remaining about 70% of the 1.15-1.25g / ml dilute sulfuric acid solution, and control the time of adding dilute sulfuric acid to about 15-20 minutes. During the second addition of dilute sulfuric acid, start vacuuming the paste machine to control the internal temperature of the paste machine not to exceed 60°C; after the acid addition is completed, stop vacuuming, restore the internal pressure of the paste machine to normal pressure, continue stirring the lead paste for about 3-5 minutes, and the paste is completed.

Citation Information

Patent Citations

  • A polypyrrole-coated conductive carbon black / indium oxide composite material, its preparation method and application

    CN114335537B

  • Graphene battery negative electrode material and preparation method thereof

    CN115911379A

  • Conductive polymer / acetylene black composite material for negative electrode of lead-acid battery, negative electrode of lead-acid battery, lead-acid battery and related preparation methods of conductive polymer / acetylene black composite material and lead-acid battery

    CN117855406A

  • Negative lead paste for lead carbon battery and negative plate

    CN108630937A

  • Negative electrode lead paste suitable for high and low temperature environments, and preparation method thereof, and lead-acid storage battery

    CN111600018A